PENGARUH HEALTH EDUCATION DENGAN PENGARUH HEALTH EDUCATION DENGAN METODE AUDIOVISUAL TERHADAP PENGETAHUAN DAN SIKAP IBU DALAM UPAYA MENCEGAH STUNTING PADA ANAK PRASEKOLAH DI DESA KALIKEJAMBON KECAMATAN TEMBELANG: PENGARUH HEALTH EDUCATION DENGAN METODE AUDIOVISUAL TERHADAP PENGETAHUAN DAN SIKAP IBU DALAM UPAYA MENCEGAH STUNTING PADA ANAK PRASEKOLAH DI DESA KALIKEJAMBON KECAMATAN TEMBELANG - Bella, Bella Dinita Rusmandani; Nofiah, Niafatun; Wahdi, Achmad; Yunita (WELL BEING, 2023)
Toddlers who have less height are characterized by delayed growth of children which results in failure to achieve normal and healthy height according to the child's age. This study aims to determine the effect of health education on knowledge and attitudes of mothers in an effort to prevent stunting in Kalikejambon Village, Tembelang District, Jombang Regency. The method used is delivering material and filling out questionnaires related to stunting prevention. The results of the study were obtained after being given education using the audiovisual method there was an increase in sufficient knowledge (64%) while a positive attitude (92%) in preventing stunting in preschoolers, with a p-value = 0.00 (p <0.05) means that the accepted means that there is a significant effect after being given health education with the audiovisual method. It is hoped that with an increase in knowledge and attitude in mothers who have stunted children, it can reduce the incidence of stunting. Keywords: Stunting, Health Education, Audiovisual Method, Knowledge and Attitudes